Exploratory Study on the Acceptance of Mobile Learning in the Commercial Banking Sector - Lai, Tze May (2024)
In the era of digitalisation, mobile learning – the use of mobile technologies to access educational content and training – has emerged as a transformative tool with significant potential benefits for various sectors. However, the commercial banking sector in Malaysia faces low adoption rates due to resistance to change, limited awareness, technical barriers, and data security concerns. This study investigates the acceptance of mobile learning among employees in the commercial banking sector, focusing on their attitudes, beliefs, and expectations. Specifically, the research aims to (i) examine the impact of mobile learning on organisational learning and improvement, (ii) investigate the perceived benefits, challenges, and expectations of employees, and (iii) explore the factors contributing to the acceptance of mobile learning. Using a qualitative methodology within the interpretivism paradigm, data were collected through semi-structured interviews, focus group discussions, and document analysis. Participants included decision makers and operational employees from various levels within the sector in the Klang Valley, encompassing Selangor and Kuala Lumpur. Data analysis techniques such as thematic analysis and constant comparative analysis were employed to identify patterns and themes. The findings reveal the perceived impact of mobile learning on organisational improvement, professional development, and operational efficiency, with varying acceptance levels among decision makers and operational employees. Key factors influencing adoption include leadership, training, and user friendly platform. A comprehensive framework is proposed, addressing these factors and providing actionable strategies for successful implementation. In conclusion, this study offers valuable insights and practical guidance for commercial banks aiming to leverage mobile learning. While the findings are specific to a case study within the commercial banking sector in Malaysia, they provide a foundation for future empirical research in other business environments. However, the study's limitations include its focus on a single sector and geographical region, which may affect the generalisability of the findings.